A comparative study of a commercially prepared dental x-ray processing solution and a self-mixed solution - Gonzales, Grace C.
A commercially prepared dental x-ray processing solution was compared with a self-mixed solution prepared from individually weighed powders. Radiographs of an x-ray analyzer were processed in the two solutions at varying lengths of time and temperature. Results show that the developing time for the commercially prepared solution is shorter and that it produced better film contrast and density than the self-mixed solution. However, the self-mixed solution was relatively cheaper.